Public attitudes toward fiscal consolidation: Evidence from a representative German Population Survey - Bernd Hayo; Florian Neumeier (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
The poor state of public finances in many countries has led to calls for fiscal consolidation. In practice, implementing concrete consolidation measures appears to meet with public resistance, suggesting that the success of consolidation efforts strongly depends on the popularity of the chosen measures. To identify public attitudes toward fiscal consolidation and alternative consolidation measures, we conducted a survey among 2,000 German citizens. Applying ordered and multinominal logit models, we test theory-based hypotheses about the determinants of individual attitudes toward public debt. We find that, inter alia, personal economic situation, time preferences, fiscal illusion, and trust in politicians exert a significant impact on attitudes toward fiscal consolidation and preferences for alternative consolidation measures.
Keywords: D72; H31; H63; 330; Public debt; fiscal consolidation; sovereign debt crisis; public attitudes; Germany